2011
DOI: 10.1590/s0100-736x2011000500009
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos clínicos e a bioquímica ruminal de caprinos submetidos à acidose láctica experimental e suplementados ou não com monensina sódica

Abstract: Objetivou-se com este trabalho estudar o comportamento clínico e laboratorial de caprinos submetidos à incorporação da monensina sódica na alimentação e avaliar os seus efeitos na prevenção da acidose láctica ruminal induzida experimentalmente. Foram avaliados os aspectos clínicos como atitude, comportamento, apetite, coloração das mucosas externas, frequência cardíaca e respiratória, motilidade retículo-ruminal, temperatura retal e o aspecto das fezes, e as características físico-químicas e microbiológicas do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
5
0
3
Order By: Relevance
“…The decrease in PVD observed after T24h occurred because of the treatment (hydration) of the animals, required in two sheep's from control group, two from monensin and one sheep from probiotic group. Dehydration caused by ruminal acidosis originates from the sharp increase in ruminal osmolality compared to blood osmolarity, which leads to the passage of fluids through the rumen (MIRANDA NETO et al, 2011;RODRIGUES et al, 2011). It is suggested that the lower degree of dehydration observed in the probiotic group (P < 0.05) is associated with the consumption of lactic acid by the yeasts present in the probiotic, which could reduce rumen osmolarity and, consequently, the flow of fluids from the blood to the rumen (RODRIGUES et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in PVD observed after T24h occurred because of the treatment (hydration) of the animals, required in two sheep's from control group, two from monensin and one sheep from probiotic group. Dehydration caused by ruminal acidosis originates from the sharp increase in ruminal osmolality compared to blood osmolarity, which leads to the passage of fluids through the rumen (MIRANDA NETO et al, 2011;RODRIGUES et al, 2011). It is suggested that the lower degree of dehydration observed in the probiotic group (P < 0.05) is associated with the consumption of lactic acid by the yeasts present in the probiotic, which could reduce rumen osmolarity and, consequently, the flow of fluids from the blood to the rumen (RODRIGUES et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…To avoid clinical and ruminal metabolism effects of ARLA in animals subjected to carbohydrate-rich diets are the addition of ionophore compounds or probiotics to the total feed (AFONSO et al, 2002;LECHTENBERG, 2007). The ionophore monensin has a selective action on bacteria such that Gram-negative bacteria can survive, while Gram-positive bacteria are inhibited (NAGARAJA et al, 1982). The Saccharomyces cerevisiae probiotics stimulate specific rumen bacteria populations, promote an increase in the cellulolytic bacteria number, stabilize the rumen pH, and increase both the fiber digestibility and the anaerobic conditions (BACH et al, 2007;DESNOYERS et al, 2009;LETTAT et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…O protocolo experimental com sacarose foi eficiente para provocar o quadro de ALRA e as fêmeas estudadas manifestaram os sinais típicos da doença, observados em casos naturais (Braun et al 1992, Vieira et al 2006, Leal et al 2007) ou induzidos (Afonso et al 2002a, 2002b, Maruta & Ortolani 2002, Miranda Neto et al 2005, Ortolani et al 2010. Apesar de a hipertermia ter sido relatada em caprinos e ovinos acometidos (Braun et al 1992, Afonso et al 2002b, Miranda Neto et al 2011, essa alteração não estava presente nos animais deste estudo.…”
Section: Discussionunclassified
“…A transfaunação é particularmente recomendada nos casos de acidose láctica ruminal aguda (ALRA), considerada a doença fermentativa pré-estomacal mais grave, uma vez que a maior parte da microbiota é destruída (Smith 2015). Este procedimento tem sido empregado nos casos naturais e de indução experimental dessa enfermidade em bovinos (Maruta & Ortolani 2002, Leal et al 2007, Ortolani et al 2010) e em pequenos ruminantes (Braun et al 1992, Vieira et al 2006, Miranda Neto et al 2011.…”
Section: Introductionunclassified
“…The preventive measures adopted for RLA include the gradual supply of carbohydrates in the diet and the use of food additives that regulate the ruminal environment, such as the ionophore antibiotics that selectively inhibit Gram-positive ruminal bacteria, among them the main producers of lactic acid, favoring the growth of Gram-negative bacteria (NAGARAJA;LECHTENBERG, 2007;RANGEL et al, 2008). Monensin sodium has been widely used in the diet of confined cattle to improve food efficiency and prevent the occurrence of acute ruminal lactic acidosis (NAGARAJA et al, 1982;LUCCI, 2000aLUCCI, , 2000b and its efficiency in the prevention of RLA has also been studied in goats, through clinical and laboratory observations, with inconsistent results (MIRANDA NETO et al, 2011).…”
Section: Introductionmentioning
confidence: 99%